Analisis Pendapatan Daerah dalam Mengukur Kemandirian Daerah Kabupaten Bandung - Fatma, Afiqah; Slamet Usman Ismanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
A region's ability to manage regional finances will influence the level of regional independence. To measure the regional independence of Bandung Regency, regional income was measured using ratio analysis consisting of the degree of decentralization ratio, the regional dependency ratio, the regional financial independence ratio, and the PAD effectiveness ratio. The method used in this research is a descriptive qualitative method using secondary data in the form of budget realization reports. The results of the research show that the regional financial performance of Bandung Regency has not been maximized with an average degree of decentralization of 18.41% with the criteria of insufficient capacity, the level of regional dependency is very high with an average of 68.45%, the average level of regional financial independence is 26.93% are included in low financial capability and have a consultative relationship pattern, the average PAD effectiveness level is 110.76% or is included in the very effective category. From the research results it can be concluded that Bandung Regency is not yet independent in managing its regional finances. Efforts that the Bandung Regency Regional Government can make to overcome this are by conducting outreach regarding tax regulations to taxpayers, exploring other potential sources of PAD revenue, and intensifying PAD revenue.